New evidence on the provenance of Red Lustrous Wheel-made Ware (RLW): Petrographic, elemental and Sr-Nd isotope analysis. (April 2019) - Kibaroğlu, Mustafa; Kozal, Ekin; Klügel, Andreas; Hartmann, Gerald; Monien, Patrick
Abstract: The Red Lustrous Wheel-made Ware (RLW) is a distinctive Late Bronze Age ware produced from high quality red clay with an array of particular forms and a polished red surface. It has a wide distribution in the Eastern Mediterranean, mainly including central Anatolia, Cilicia, Cyprus, the Levant, and Egypt, indicating the important role of the ware in displaying possible cultural, commercial, and political interconnections. Its unique and identical character throughout its distribution area still complicates the identification of its provenance. Therefore, it has been the subject of numerous archaeological and archaeometric studies. In previous archaeological studies, a Cypriot origin for the ware has been proposed and generally accepted. In comparison to archaeological research, Cyprus and/or Anatolia are suggested as the origin of RLW in previous archaeometric studies. However, the latest discoveries from Anatolia suggests that the production place of RLW could be located in Rough Cilicia in southern Anatolia, as new RLW forms have been identified at Kilise Tepe level III (1500–1300 BCE). This study focuses on the newly identified RLW forms of jar and its subgroups excavated at Kilise Tepe, level III (c. 1500–1300 BCE). We report archaeometric results of petrographic, trace element and Sr ( 87 Sr/ 86 Sr) and Nd ( 143 Nd/ 144 Nd) isotopic analysis of RLW samples, not only from Kilise Tepe in southern Anatolia but also from Boğazköy/Ḫattuša in central Anatolia, and Tell Atchana/Alalakh in the Amuq Plain as comparative material. Archaeometric results suggest that the new RLW forms with their subgroups belong to the main chemical and mineralogical corpus of RLW. These results support the thesis that Kilise Tepe is the site with the largest variety of RLW forms, and also the hypothesis that the origin of RLW might be in Rough Cilicia in southern Anatolia. A few samples from each site were defined as outliers, indicating that there are small amounts of RLW produced from other clays, the sources of which remain unidentified. Highlights: The Lustrous Wheel-made ware (RLW) and new identified RLW forms were analyzed using petrographic, LA-ICP-MS, Sr-Nd isotope methods The results suggest that the Red Lustrous Wheel-made ware (RLW) was produced in South Anatolia The study shows also that the Sr and Nd isotope analysis is as a useful tool for provenance study of archaeological ceramic